Compact, High-Speed Mach-Zehnder Modulator with On-Chip Linear Drivers in Photonic BiCMOS Technology - Kress, Christian; Schwabe, Tobias; Rhee, Hanjo; Scheytt, J. Christoph (IEEE Access)

Generation of 100 GHz Periodic Nyquist Pulses using Cascaded Mach-Zehnder Modulators in a Silicon Electronic-Photonic Platform - Kress, Christian; Schwabe, Tobias; Silberhorn, Christine; Scheytt, J. Christoph (Conference on Lasers and Electro-Optics (CLEO) 2023)
A frequency-flexible Nyquist pulse synthesizer is presented with optical pulse bandwidths up to fopt=100 GHz and repetition rates equal to fopt/9, fabricated in an electronic-photonic co-integrated platform utilizing linear on-chip drivers.

Analysis of Phase Noise in Waveguide-integrated Optical Test Structures in Silicon Photonics - Surendranath Shroff, Vijayalakshmi; Kress, Christian; Bahmanian, Meysam; Scheytt, J. Christoph (2023 PhotonIcs & Electromagnetics Research Symposium (PIERS),)
This paper experimentally investigates and interprets the e®ects of noise and non- linearity in a silicon photonic optical test structure. For the analysis di®erent optoelectronic phase noise measurement techniques are used. Our tests focuses on the performance of integrated opti- cal test structures using femtosecond pulses in the 1550nm spectral range. A primary objective is to understand the behaviour of silicon photonic waveguides that can be further employed in the implementation of an optoelectronic phase-locked loop (OEPLL) in silicon photonics technology. A comparison of our results, as well as a discussion on the di®erent optoelectronic phase noise measurement techniques are presented. Our ¯ndings provide insights that can be leveraged to optimize the design and performance of ultra-low phase noise on-chip OEPLL systems locking to mode-locked laser (MLL) signals. In the future such systems can be essential for advanced communication and sensing applications.

Locking of microwave oscillators on the interharmonics of mode-locked laser signals - Bahmanian, Meysam; Kress, Christian; Scheytt, Christoph (Optics Express)
In this paper, the theory of phase-locking of a microwave oscillator on the interharmonics, i.e. non-integer harmonics, of the repetition rate of the optical pulse train of a mode-locked laser (MLL) is developed. A balanced optical microwave phase detector (BOMPD) is implemented using a balanced Mach-Zehnder modulator and is employed to discriminate the phase difference between the envelope of the optical pulses and the microwave oscillator. It is shown mathematically that the inherent nonlinear properties of BOMPD with respect to the microwave excitation amplitude can be used for interharmonic locking. The characteristic functions of the phase detector for interharmonic locking are derived analytically and are compared with the measurement results. An opto-electronic phase-locked loop (OEPLL) is demonstrated whose output frequency locks on interharmonics of the MLL repetition rate when an appropriate modulator bias and sufficient RF amplitude are applied. Thus, for the first time theory and experiment of reliable locking on interharmonics of the repetition rate of a MLL are presented.

Reconfigurable and real-time high-bandwidth Nyquist signal detection with low-bandwidth in silicon photonics - Misra, Arijit; Kress, Christian; Singh, Karanveer; Meier, Janosch; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Optics Express)
We demonstrate for the first time, to the best of our knowledge, reconfigurable and real-time orthogonal time-domain detection of a high-bandwidth Nyquist signal with a low-bandwidth silicon photonics Mach-Zehnder modulator based receiver. As the Nyquist signal has a rectangular bandwidth, it can be multiplexed in the wavelength domain without any guardband as a part of a Nyquist-WDM superchannel. These superchannels can be additionally multiplexed in space and polarization. Thus, the presented demonstration can open a new possibility for the detection of multidimensional parallel data signals with silicon photonics. No external pulse source is needed for the receiver, and frequency-time coherence is used to sample the incoming Nyquist signal with orthogonal sinc-shaped Nyquist pulse sequences. All parameters are completely tunable in the electrical domain. The feasibility of the scheme is demonstrated through a proof-of-concept experiment over the entire C-band (1530 nm–1560 nm), employing a 24 Gbaud Nyquist QPSK signal due to experimental constraints on the transmitter side electronics. However, the silicon Mach-Zehnder modulator with a 3-dB bandwidth of only 16 GHz can process Nyquist signals of 90 GHz optical bandwidth, suggesting a possibility to detect symbol rates up to 90 GBd in an integrated Nyquist receiver.

Flexible Time-Domain De-Multiplexing of Nyquist OTDM Channels by Orthogonal Sampling in Silicon Photonics - Misra, Arijit; Singh, Karanveer; Meier, Janosch; Kress, Christian; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Conference on Lasers and Electro-Optics)
We report for the first time, inter-symbol-interference (ISI) free demultiplexing of Nyquist optical time division multiplexed (OTDM) signals using a reconfigurable orthogonal sinc-pulse sampling enabled by silicon photonic Mach-Zehnder Modulators.

Analysis of the effect of jitter and non-idealities on photonic digital-to-analog converters based on Nyquist pulses - Singh, Karanveer; Kress, Christian; Mandalawi, Younus; Misra, Arijit; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Next-Generation Optical Communication: Components, Sub-Systems, and Systems XI)

Emulation of integrated high-bandwidth photonic AWG using low-speed electronics - Singh, Karanveer; Meier, Janosch; Kress, Christian; Misra, Arijit; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Next-Generation Optical Communication: Components, Sub-Systems, and Systems XI)

Locking of microwave oscillators on the interharmonics of mode-locked laser signals - Bahmanian, Meysam; Kress, Christian; Scheytt, J. Christoph (Optics Express)
In this paper, the theory of phase-locking of a microwave oscillator on the interharmonics, i.e. non-integer harmonics, of the repetition rate of the optical pulse train of a mode-locked laser (MLL) is developed. A balanced optical microwave phase detector (BOMPD) is implemented using a balanced Mach-Zehnder modulator and is employed to discriminate the phase difference between the envelope of the optical pulses and the microwave oscillator. It is shown mathematically that the inherent nonlinear properties of BOMPD with respect to the microwave excitation amplitude can be used for interharmonic locking. The characteristic functions of the phase detector for interharmonic locking are derived analytically and are compared with the measurement results. An opto-electronic phase-locked loop (OEPLL) is demonstrated whose output frequency locks on interharmonics of the MLL repetition rate when an appropriate modulator bias and sufficient RF amplitude are applied. Thus, for the first time theory and experiment of reliable locking on interharmonics of the repetition rate of a MLL are presented.

Broadband Mach-Zehnder Modulator with Linear Driver in Electronic-Photonic Co-Integrated Platform - Kress, Christian; Schwabe, Tobias; Rhee, Hanjo; Kerman, Sarp; Scheytt, J. Christoph (Optica Advanced Photonics Congress 2022)
A monolithically integrated electronic-photonic Mach-Zehnder modulator is presented, incorporating electronic linear drivers along photonic components. An electro-optical 3 dB & 6 dB bandwidth of 24 GHz and 34 GHz respectively was measured. The on-chip drivers decrease the V π by a factor of 10.

Towards an IEEE 802.11 Compliant System for Outdoor Vehicular Visible Light Communications - Amjad, Muhammad Sohaib; Tebruegge, Claas; Memedi, Agon; Kruse, Stephan; Kress, Christian; Scheytt, J. Christoph; Dressler, Falko (IEEE Transactions on Vehicular Technology)
As a complementary technology to existing Radio Frequency (RF)-based solutions such as Cellular V2X (C-V2X) and Dedicated Short Range Communication (DSRC), Vehicular VLC (V-VLC) is gaining more attention in the research community as well as in the industry. This paper introduces a complete IEEE 802.11 compliant V-VLC system. The system relies on Universal Software Radio Peripheral (USRP) software defined radios programmed using the GNU Radio framework, a typical car headlight plus a custom driver electronics for the high-power car LEDs (sender), and a photodiode (receiver). Building upon our earlier work, we, for the first time, experimentally explore the communication performance in outdoor scenarios, even in broad daylight, and show that rather simple optical modifications help to reduce the ambient noise to enable long distance visible light communication. Our system also supports Orthogonal Frequency-Division Multiplexing (OFDM) with a variety of Modulation and Coding Schemes (MCS) up to 64-QAM and is fully compliant with IEEE 802.11. We performed an extensive series of experiments to explore the performance of our system, even using higher order MCS in daylight. Our results demonstrated a high reliability for distances up to 75m with the presented system, regardless of the time of the day.

Roll-Off Factor Analysis of Optical Nyquist Pulses Generated by an On-Chip Mach-Zehnder Modulator - De, Souvaraj; Singh, Karanveer; Kress, Christian; Das, Ranjan; Schwabe, Tobias; Preußler, Stefan; Kleine-Ostmann, Thomas; Scheytt, J. Christoph; Schneider, Thomas (IEEE Photonics Technology Letters)

Phase Noise Investigation for a Radar System with Optical Clock Distribution - Kruse, Stephan; Bahmanian, Meysam; Kneuper, Pascal; Kress, Christian; Kurz, Heiko G.; Schneider, Thomas; Scheytt, Christoph (The 17th European Radar Conference)

High Modulation Efficiency Segmented Mach-Zehnder Modulator Monolithically Integrated with Linear Driver in 0.25 \textmum BiCMOS Technology - Kress, Christian; Singh, Karanveer; Schwabe, Tobias; Preußler, Stefan; Schneider, Thomas; Scheytt, J. Christoph (OSA Advanced Photonics Congress 2021)
We present a monolithically integrated electronic-photonic Mach-Zehnder modulator with a linear, segmented driver on the same silicon substrate. As metric for the modulation efficiency, the external V$π$ is hereby reduced to only 420 mV.
Keywords: Analog to digital converters; Extinction ratios; Grating couplers; Modulation; Modulators; Phase shift

Analysis of the effects of jitter, relative intensity noise, and nonlinearity on a photonic digital-to-analog converter based on optical Nyquist pulse synthesis - Kress, Christian; Bahmanian, Meysam; Schwabe, Tobias; Scheytt, J. Christoph (Opt. Express)
An analysis of an optical Nyquist pulse synthesizer using Mach-Zehnder modulators is presented. The analysis allows to predict the upper limit of the effective number of bits of this type of photonic digital-to-analog converter. The analytical solution has been verified by means of electro-optic simulations. With this analysis the limiting factor for certain scenarios: relative intensity noise, distortions by driving the Mach-Zehnder modulator, or the signal generator phase noise can quickly be identified.
Keywords: Analog to digital converters; Diode lasers; Laser sources; Phase noise; Signal processing; Wavelength division multiplexers

Reconfigurable and Real-Time Nyquist OTDM Demultiplexing in Silicon Photonics - Misra, Arijit; Singh, Karanveer; Meier, Janosch; Kress, Christian; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Electrical Engineering and Systems Science)
We demonstrate for the first time, to the best of our knowledge, reconfigurable and real-time orthogonal time-domain demultiplexing of coherent multilevel Nyquist signals in silicon photonics. No external pulse source is needed and frequencytime coherence is used to sample the incoming Nyquist OTDM signal with orthogonal sinc-shaped Nyquist pulse sequences using Mach-Zehnder modulators. All the parameters such as bandwidth and channel selection are completely tunable in the electrical domain. The feasibility of this scheme is demonstrated through a demultiplexing experiment over the entire C-band (1530 nm - 1550 nm), employing 24 Gbaud Nyquist QAM signals due to experimental constraints on the transmitter side. However, the silicon Mach-Zehnder modulator with a 3-dB bandwidth of only 16 GHz can demultiplex Nyquist pulses of 90 GHz optical bandwidth suggesting a possibility to reach symbol rates up to 90 GBd in an integrated Nyquist transceiver.

Optical PRBS Generation with Threefold Bandwidth of the Employed Electronics and Photonics - Singh, Karanveer; Meier, Janosch; Preussler, Stefan; Kress, Christian; Scheytt, J. Christoph; Schneider, Thomas (OSA Advanced Photonics Congress 2021)
We present the optical generation of a 300 Gbaud PRBS-7 data signal based on time-division multiplexing of Nyquist sinc-pulse sequences. The employed electronic and photonic components need only one-third of the final bandwidth.

Analysis and Simulation of a Wireless Phased Array System with Optical Carrier Distribution and an Optical IQ Return Path - Kruse, Stephan; Kress, Christian; Scheytt, Christoph; Kurz, Heiko G.; Schneider, Thomas (GeMiC 2020 - German Microwave Conference)
In this paper we present a new system concept for an optoelectronic wireless phased array system. Like in a conventional phased array system with optical carrier distribution, optical fibers are used to distribute the carrier from the basestation to the wireless frontends. However in contrast to prior concepts, we propose to use an optical IQ return path from the wireless frontends back to the basestation. Furthermore, we reuse the optical carrier signal for the IQ return path which allows to avoid local oscillator lasers in the wireless frontends and reduces the hardware effort significantly. The system concept allows to integrate all components of an optoelectronic wireless frontend in a single chip using silicon photonics technology.

An IEEE 802.11 Compliant SDR-Based System for Vehicular Visible Light Communications - Amjad, Muhammad Sohaib; Tebruegge, Claas; Memedi, Agon; Kruse, Stephan; Kress, Christian; Scheytt, Christoph; Dressler, Falko (IEEE International Conference on Communications (ICC))
We present a complete Visible Light Communication (VLC) system for experimental Vehicular VLC (V-VLC) research activities. Visible light is becoming an important technology complementing existing Radio Frequency (RF) technologies such as Cellular V2X (C-V2X) and Dedicated Short Range Communication (DSRC). In this scope, first works helped introducing new simulation models to explore V-VLC capabilities, technologies, and algorithms. Yet, experimental prototypes are still in an early phase. We aim bridging this gap with our system, which integrates a custom-made driver hardware, commercial vehicle light modules, and an Open Source signal processing implementation in GNU Radio, which explicitly offers rapid prototyping. Our system supports OFDM with a variety of Modulation and Coding Schemes (MCS) and is compliant to IEEE 802.11; this is in line with the upcoming IEEE 802.11 LC standard as well. In an extensive series of experiments, we assessed the communication performance by looking at realistic inter vehicle distances. Our results clearly show that our system supports even higher order MCS with very low error rates over long distances.

Integrated All Optical Sampling of Microwave Signals in Silicon Photonics - Misra, Arijit; Kress, Christian; Singh, Karanveer; Preussler, Stefan; Scheytt, Christoph; Schneider, Thomas (2019 International Topical Meeting on Microwave Photonics (MWP))
Optical sampling of pseudo random microwave signals with sinc-shaped Nyquist pulse sequences has been demonstrated in an integrated silicon photonics platform. An electronic-photonic, co-integrated depletion type silicon intensity modulator with high extinction ratio has been used to sample the microwave signal with a sampling rate, which corresponds to three times its RF bandwidth. Thus, a sampling rate of 21 GSa/s is achieved with a 7 GHz modulator, with 3 dBm of differential input power.

Integrated source-free all optical sampling with a sampling rate of up to three times the RF bandwidth of silicon photonic MZM - Misra, Arijit; Kress, Christian; Singh, Karanveer; Preussler, Stefan; Scheytt, Christoph; Schneider, Thomas (Opt. Express)
Source-free all optical sampling, based on the convolution of the signal spectrum with a frequency comb in an electronic-photonic, co-integrated silicon device will be presented for the first time, to the best of our knowledge. The method has the potential to achieve very high precision, requires only low power and can be fully tunable in the electrical domain. Sampling rates of three and four times the RF bandwidths of the photonics and electronics can be achieved. Thus, the presented method might lead to low-footprint, fully-integrated, precise, electrically tunable, photonic ADCs with very high-analog bandwidths for the digital infrastructure of tomorrow.

First Performance Insights on Our Noval OFDM-based Vehicular VLC Prototype - Koepe, Jörn; Kaltschmidt, Christian; Illian, Marvin; Puknat, Robert; Kneuper, Pascal; Wittemeier, Steffen; Memedi, Agon; Tebruegge, Claas; Amjad, Muhammad Sohaib; Kruse, Stephan; Kress, Christian; Scheytt, Christoph; et al. (2018 IEEE Vehicular Networking Conference (VNC))
In this poster, we present the first experimental results of our OFDM-based Vehicular VLC (V-VLC) prototype. Our Bit Error Rate (BER) measurements show that for lower Modulation and Coding Schemes (MCS), the performance of our hardware-setup roughly behaves the same as it does in simulation for AWGN channel. However, for higher order MCS with high PAPR, the BER performance gets degraded due to non-linear behavior of LEDs, and deviates further from AWGN performance as the MCS order is increased. The obtained results suggest that unlike RF-Communications, where the focus is usually towards linearity of the amplifiers, for V-VLC, linearity within the whole system is required to achieve optimal performance.

Design of an Automotive Visible Light Communications Link using a Off-The-Shelf LED Headlight - Kruse, Stephan; Kress, Christian; Memedi, Agon; Tebruegge, Claas; Amjad, Muhammad Sohaib; Scheytt, Christoph; Dressler, Falko (ANALOG 2018 16. GMM/ITG-Fachtagung)
We present a transmitter circuit to drive a commercial Light Emitting Diode (LED)-based headlight for automotive Visible Light Communication (VLC). Based on the design of the presented transmitter (TX), we provide a design methodology for VLC TXs and make it available as Open Hardware. Furthermore, a complete wireless VLC link is built using the GNU Radio signal processing tool chain and demonstrated on an Universal Software Radio Peripheral (USRP). The Total Harmonic Distortion (THD) of the system is below 5% for a wide input voltage range and the 1 dB compression point (P1dB) is at 1.02V, which makes the circuit attractive for more advanced modulation formates like Orthogonal Frequency Division Multiplexing (OFDM) or Pulse-Amplitude Modulation (PAM).

64 GBd Monolithically Integrated Coherent QPSK Single Polarization Receiver in 0.25 µm SiGe-Photonic Technology - Kress, Christian; Gudyriev, Sergiy; Zwickel, Heiner; Kemal, Juned N.; Lischke, Stefan; Zimmermann, Lars; Koos, Christian; Scheytt, Christoph (Optical Fiber Communication Conference 2018, San Diego)
A monolithically integrated coherent receiver in silicon photonic technology is presented along with measurement results for constellation diagrams up to 64GBd and bandwidth of 34 GHz. To our knowledge this is the fastest single-chip coherent receiver.

Electronic Photonic Integrated Circuits for Coherent and Non-Coherent Receivers - Gudyriev, Sergiy; Kress, Christian; Scheytt, Christoph (10th Sino-German Joint Symposium on Opto- and Microelectronic Devices and Circuits (SODC 2018))

Electronic‐Photonic Integrated Systems for Ultrafast Signal Processing - Gudyriev, Sergiy; Kress, Christian; Scheytt, Christoph (DFG Priority Programme SPP2111)

Coherent ePIC Receiver for 64 GBaud QPSK in 0.25μm Photonic BiCMOS Technology - Gudyriev, Sergiy; Kress, Christian; Zwickel, Heiner; Kemal, Juned N.; Lischke, Stefan; Zimmermann, Lars; Koos, Christian; Scheytt, Christoph (IEEE/OSA Journal of Lightwave Technology)
In this paper, we present a monolithically integrated coherent receiver with on-chip grating couplers, 90° hybrid, photodiodes and transimpedance amplifiers. A transimpedance gain of 7.7 kΩ was achieved by the amplifiers. An opto-electrical 3 dB bandwidth of 34 GHz for in-phase and quadrature channel was measured. A real-time data transmission of 64 GBd-QPSK (128 Gb/s) for a single polarization was performed.

Fully-Differential, Hybrid, Multi-channel 4x25Gbps Direct Direction Receiver in 0.25\textmum BiCMOS SiGe Technology - Gudyriev, Sergiy; Scheytt, Christoph; Kress, Christian; Yan, Lei; Christian, Meuer; Zimmermann, Lars (OSA Frontiers in Optics + Laser Science)
A hybrid multi-channel receiver featuring fully-differential transimpedance input stages for 25Gbps data rate per channel is presented along with measurement results focusing on the channel-to-channel interference and sensitivity. OMA of -16dBm at a BER of 10−4 is estimated at the photodiode for all channels. Each channel dissipates 330mW of power provided from a single 3.3V supply voltage.